Peningkatan Kesadaran Keagamaan Anak Anak Melalui Pembinaan Adab dan Akhlak Agama Islam di Desa Selemak Hamparan Perak - Rezky Yudha Septian; Nadhira Ayu Putri Sikumbang; Nur Nazwa (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2025)
Education serves as an institutional mechanism that can accelerate the development of a nation's character. Factors influencing the decline of the Indonesian nation are the result of mental and moral decline, which occurs in both the older and younger generations, including within the government and among the wider community. These factors have resulted in the Indonesian nation experiencing setbacks in various positions in the world. To overcome this problem, the Indonesian nation needs to develop and build a life by instilling positive values ​​​​to develop good character and be able to compete with other countries in the era of globalization. Character education offers a great opportunity to implement the process of fostering and developing human beings, with education based on noble morals, namely Islamic education that integrates faith, sharia, and morals in a learning system that is based on Islamic morals and influences self-improvement. One of the advantages of Al-Islam for humanity is the creation of a comprehensive and consistent method for developing mentality, producing generations, building society and culture, and upholding the principles of glory and civilization. Child educators must continue to seek more effective methods, seeking informative educational rules in preparing children mentally and morally, scientifically, spiritually, and socially, so that children can reach perfect maturity.